PENDAMPINGAN PEMBUATAN TIE-DYE ATAU BATIK CELUP PADA SISWA SEKOLAH DASAR NEGERI SUMBERDUREN KECAMATAN TAROKAN - Rosita Rahmawati, Novi; Yusal, Yulianti; Anggraini, Atika; Agustina, Niken (Proceedings of Annual Conference on Community Engagement, 2024)
Education is an unavoidable obligation for individuals to build self-quality. In this modern era, education can be accessed flexibly. However, the importance of developing innovation and creativity is often overlooked. Students of KKN Group 22 at IAIN Kediri deal with the problem of a lack of emphasis on innovation and creativity at SDN Sumberduren Tarokan. The method for implementing community empowerment activities uses the ABCD (Asset Bassed Community Development) method which emphasizes asset development. They use a white tote bag as a medium in tie-dye learning, helping students from every stage of making to coloring. This activity aims to strengthen students' innovative and creative abilities as well as motor skills. The results include dividing the totebags, wetting, folding with a spiral pattern, coloring, storage for 24 hours, to washing and drying the totebags. The results of the training show the active participation of students and an increase in their understanding of innovation and creativity. Thus, making tie-dye or dyed batik for elementary school students can foster a creative spirit in students and also foster an entrepreneurial spirit from an early age to face challenges and competition in the future.